Preparation of Dye-Sensitized Solar Cell (DSSC) Using TiO2 and Mahkota Dewa Fruit (Phaleria Macrocarpa (Scheff) Boerl.) Extract - Hindryawati, Noor; Hiyahara, Irfan Ashari; Saputra, Herdian; Arief, M. Syaiful; Maniam, Gaanty Pragas (Universitas Negeri Semarang, 2021)
A dye sensitized solar cell (DSSC) is a low-cost solar cell with attractive features. DSCC contains of photoelectrode, dye, electrolyte, and counter electrode with photoelectrochemical system. The aim of this research is to determine the percent efficiency produced by DSSC from the Mahkota Dewa extract. This was carried out in various stages, namely sample preparation and extraction, DSSC assembly, TiO2 characterization using Scanning Electron Microscopy (SEM), and testing its current and voltage. The results showed that the maximum wavelength of the Mahkota Dewa extract dye test using a UV-Vis spectrophotometer was 554 nm with an absorbance of 0.163, which was believed to be the wavelength of flavonoid and anthocyanin compounds. Based on the characterization results, surface morphology was spherical and agglomerated. However, after being soaked in the dye, the surface morphology of the TiO2 layer did not appear spherical on the surface that was expected to have been covered by the dye. The measurement using sunlight sources showed that the maximum current and voltage of DSSC with a concentration of 30% w/v was 21.8x10-4A and 58.86 V with an efficiency of 22.43x10-3 %. In addition, there was a 0.482% decrease in DSSC efficiency based on the storage time which lasted for a period of 6 days.